Callicles' pleonexia - Kaluđerović Željko; Donev Dejan (Kom: Časopis za Religijske Nauke, 2016)
The authors begin the paper by discussing Callicles' critique of the forms of government and of political action in its entirety, which he, unlike Protagoras, established upon the concept of natural justice. Following Callicles' justification, the authors conclude that truly just man is not the one of democratic or monarchist views but the one who is a ruthless and cruel tyrant, and that pleonexia is the first and fundamental principle of human nature. Callicles presented the natural justice in accordance with the possible subjective states and processes of human consciousness, so that people are not equal by nature; he understood justice as the right of the superior, better and stronger. By praising greed, covetousness, avarice and freedom as virtue and happiness, Callicles also denounced the understanding of arithmetic and geometric equality, as well as one of the foundations on which rested the presentation and understanding of justice, that is the idea of equivalence. Through such views of Callicles, finally, the sophistic view is brought to its radical consequences, while the understanding of individual justice which he represents, to the extreme.